Water‐Dependent Selective Synthesis of Mono‐ or Bis‐Selanyl Alkenes from Terminal Alkynes. Issue 14 (9th September 2016) - Luz, Eduardo Q.; Lopes, Eric F.; Ricordi, Vanessa G.; Santi, Claudio; Barcellos, Thiago; Lenardão, Eder J.; Perin, Gelson; Alves, Diego
Abstract: We described here an alternative method for the selective synthesis of mono‐ or bis‐selanyl alkenes. This method involves reactions of terminal alkynes with organylselenols, generated in situ by the reaction of diorganyl diselenides with H3 PO2 . These reactions proceeded efficiently at 90 °C under N2 atmosphere and are suitable to a range of diorganyl diselenides and terminal alkynes, both containing electron‐withdrawing and electron‐donating groups, affording the corresponding mono‐ or bis‐selanyl alkenes in good yields and selectively. When the reactions were performed using 5.0 equiv. of H3 PO2 (0.5 mL; 50 wt% in H2 O), mono‐selanyl alkenes were formed in good yields, whereas reactions carried out with additional H2 O as the solvent (3.0 mL/mmol) provided bis‐selanyl alkenes in high yields. Additionally, the solvent/reducing agent system (H2 O/H3 PO2 ) could be recovered and directly reused for further reactions to synthesize bis‐selanyl alkenes. Abstract : An alternative method for the selective synthesis of mono‐ or bis‐selanyl alkenes is described. This protocol involves reactions of terminal alkynes with in situ generated organylselenols. The identity of the adduct is dependent of the amount of water present in the reaction media. The solvent/reducing agent system was recovered and directly reused for further reactions to synthesize bis‐selanyl alkenes.